Human Resource Management in the Batik Industry: Evaluating the Role of Training and Development in Indonesia - Sholihin, Teguh Adhe; Fazriyani, Fanesha; Fadhilah, Amalia Rachmawati Nur; Firdaus, Shafira Maharani (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
The article titled Human Resource Management in the Batik Industry: Evaluating the Role of Training and Development in Indonesia" examines the impact of training and development programs on the competencies and productivity of workers in Indonesia's batik industry, primarily composed of micro, small, and medium enterprises. By analyzing qualitative data from literature over the past decade, the study highlights the benefits of human resource development through targeted training programs. These programs aim to enhance technical skills, managerial abilities, and innovative capacities among batik artisans. The findings indicate that effective training contributes to increased productivity, product quality, and competitiveness of batik MSMEs, ultimately supporting both local economic development and the preservation of Indonesia's cultural heritage. This research underscores the need for sustainable human resource practices in the batik industry to maintain its cultural significance and economic viability.